2015
DOI: 10.1186/s12992-015-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Ebola Virus Disease in West African countries not yet affected: perspectives from Ghanaian health professionals

Abstract: BackgroundThe current Ebola Virus Disease (EVD) epidemic has ravaged the social fabric of three West African countries and affected people worldwide. We report key themes from an agenda-setting, multi-disciplinary roundtable convened to examine experiences and implications for health systems in Ghana, a nation without cases but where risk for spread is high and the economic, social and political impact of the impending threat is already felt.DiscussionParticipants’ personal stories and the broader debates to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…This led to a series of surveillance training workshops and creation of an Ebola incident management system which is thought to have enhanced preparedness and reduced Ebola case burden in the region compared to other areas of the country. (Jacobsen et al, 2016;Kaufman, 2008;Zumla et al, 2016) − Indicator based surveillance (Balajee et al, 2016;Kruk et al, 2015;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015) − Event based surveillance (Adokiya & Awoonor-Williams, 2016;Balajee et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Garcia Serpa Osorio-de-Castro, Silva Miranda, Machado de Freitas, Rochel de Camargo, & Cranmer, 2017;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Stoto et al, 2013;Thiam et al, 2015), with use of community health monitors (Balajee et al, 2016;Jacobsen et al, 2016;Martineau, 2016;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Scott et al, 2016;Thiam et al, 2015) − Verification of reported signal events (Balajee et al, 2016;Espinal et al, 2016;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Siedner et al, 2015) − Appropriate referral of suspected cases (Siekmans et al, 2017;Thiam et al, 2015...…”
Section: Surveillancementioning
confidence: 99%
See 3 more Smart Citations
“…This led to a series of surveillance training workshops and creation of an Ebola incident management system which is thought to have enhanced preparedness and reduced Ebola case burden in the region compared to other areas of the country. (Jacobsen et al, 2016;Kaufman, 2008;Zumla et al, 2016) − Indicator based surveillance (Balajee et al, 2016;Kruk et al, 2015;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015) − Event based surveillance (Adokiya & Awoonor-Williams, 2016;Balajee et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Garcia Serpa Osorio-de-Castro, Silva Miranda, Machado de Freitas, Rochel de Camargo, & Cranmer, 2017;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Stoto et al, 2013;Thiam et al, 2015), with use of community health monitors (Balajee et al, 2016;Jacobsen et al, 2016;Martineau, 2016;McPake et al, 2015;Nyarko et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Scott et al, 2016;Thiam et al, 2015) − Verification of reported signal events (Balajee et al, 2016;Espinal et al, 2016;Lapao et al, 2015;Nyenswah et al, 2016;Regmi et al, 2015;Siedner et al, 2015) − Appropriate referral of suspected cases (Siekmans et al, 2017;Thiam et al, 2015...…”
Section: Surveillancementioning
confidence: 99%
“…Adequate staff numbers: doctors, nurses, CHWs (Adokiya & Awoonor-Williams, 2016;Boozary et al, 2014;Cancedda et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Gostin & Friedman, 2015;Kieny et al, 2014;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Mulinge & Soyemi, 2016;Regmi et al, 2015;Siedner et al, 2015;Siekmans et al, 2017); also at sub-regional level (Gostin & Friedman, 2015;Kruk et al, 2015;Regmi et al, 2015) . Health worker training and continuing education (Adokiya & Awoonor-Williams, 2016;Boozary et al, 2014;Cancedda et al, 2016;Espinal et al, 2016;Forrester et al, 2014;Gostin & Friedman, 2015;Kruk et al, 2015;Lapao et al, 2015;McPake et al, 2015;Mulinge & Soyemi, 2016;Nyarko et al, 2015;Regmi et al, 2015;Siedner et al, 2015;Siekmans et al, 2017;Thiam et al, 2015); understanding of community knowledge and beliefs (Buseh et al, 2015;Dhillon & Kelly, 2015;Martineau, 2016;Regmi et al, 2015;Scott et al, 2016;Thiam et al, 2015) . Traditional healers trained in infection control and public health messages (Alexander et al, 2015;McPake...…”
Section: Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…4 At the beginning of the outbreak, HCWs did not have the ability to practise and maintain a safe working environment, and infection prevention and control (IPC) measures were limited; no IPC policies or guidelines existed and no routine evaluations of IPC were conducted in health facilities prior to the EVD outbreak. [5][6][7][8] Due to the large number of deaths among health staff and the loss of community confidence in the health system, many health facilities closed completely during the outbreak. 9 The EVD outbreak and the ensuing breakdown of the health system, the high burden of EVD among HCWs, the fact that health facilities acted as drivers of EVD transmission during the outbreak, 10 and the closure of health facilities, all highlighted the importance and the necessity of IPC as the only measure capable of protecting patients, visitors, care givers, frontline HCWs and crucial health facilities in the face of a deadly outbreak.…”
mentioning
confidence: 99%